La atención en el rendimiento escolar de los niños y niñas del tercer grado paralelo B, de la escuela de educación básica Benigno Bayancela del sector San Cayetano Bajo de la ciudad de Loja. Periodo marzo-diciembre del 2014 - Castillo Masache, Carmen María (2015)
This so-called investigation: care in the school performance of children from third grade side "B", sector San Cayetano "Benigno Bayancela" elementary school low from the city of Loja. Period March-December 2014, is descriptivo-explicativo type, was raised as a general objective, know the relationship between care and school performance of children from third grade side "B". Methods was used as the scientist, analitico-sintetico, inductive, qualitative and quantitative. Jointly used techniques and instruments such as: care faces test, applied to children, and the systematization of information from the records of scores of the students. They worked with a total sample 19 boys and girls in the third grade. The application of the various instruments and the quantitative-qualitative organization of the information obtained, leads to the conclusion, that care affects the academic performance of children, since the divided attention that students present relates to a level of school performance AAR (reach the required learning), while selective attention relates to a best level of school performance located in DAR (dominate required apprenticeships); also it has been determined that the sample investigated, mostly presented a kind of divided attention, which limits its ability to assist a goal or specific activity; and that the level of achievement of the majority of the students is AAR (reach required apprenticeships). So it is recommended to teachers, classes that provide for its students to be short and teaching since it would avoid certain distracting stimuli, thus keep the attention of the children so they can reach a better level of school performance.